Electrical Impedance Value Analysis on Formalinized Tilapia Fish Meat - Putri, Rizka Rahmatie Agusta; Widodo, Chomsin Sulistya; Santoso, Didik Rahadi (Natural B, Journal of Health and Environmental Sciences, 2016)
Electrical impedance can be used as a non-destructive method to determine the bio-electrical characteristics on biological materials. Analysis of the electrical impedance value by using an electrode needle method has been applied to the tilapia flesh which aims to determine the bio-electrical characteristics on tilapia flesh, and determine the effect of formalin on it. The measurements were carried out to compare the characteristics of bio-electrical characteristics of the fresh tilapia flesh, the tilapia flesh soaked in formalin, and the one that was lay without any preservation treatment at a 10 Hz - 200 kHz frequency. The result shows that the impedance value characteristics of the fresh tilapia flesh decreased as long as the increase of frequency. Both the preserved and the rotten tilapia flesh have the decreased impedance value. The concentration of formalin immersion is directly proportional with the value of electrical impedance.Â Â